Immunohystochemical profile of cytokeratins (5, 7, 14, 18, 20) in retrospective cases of breast fibroadenomas - Marcia Bernardo; Andreia Fabiana do Vale Franco; Gil Facina; Angela Flavia Logullo Waitzberg (Annals of Cytology and Pathology - Peertechz Publications, 2020)
Introduction: Fibroadenomas (FAs) are the most common benign tumors in the breast. Described as a biphasic stromal and epithelial lesion, it is usually stable and clinically well managed. Although the cytokeratins (CKs) distribution among ductal cells is well described in carcinomas and normal breast tissue, in FAs the differentiation and distribution of epithelium CK profile is scarcely known.  Objectives: To analyze the immunoexpression of the cytokeratin profile (5, 7, 14, 18 and 20); to evaluate whether the CK5+ and CK14+ cells (progenitor cell markers) population is preserved and comparable to normal breast tissue.  Materials and methods: A retrospective observational linear study of FAs diagnosed and surgically treated at Perola Byington Hospital, São Paulo, Brazil (January and March/2006) was evaluated. Paraffin embedded tumor samples of 104 cases were included in a tissue microarray. CKs expression was assessed by counting the positive and negative number of ductal cells contained in terminal ductal acinar units and also registering the basal or luminal position of positive cells. Ki67 expression score evaluated the contingent of positive cells in 100 epithelial cells.  Results: FA epithelial component showed positive expression to CK5, 7, 14 and 18, and negative expression to CK20. Stromal cells were always negative for see these markers. The percentage and distribution of positive cells were comparable to the normal breast profile. Progenitor cells contingent was equal or higher than in normal breast tissue. Proliferation score in FAs was maintained comparable to the normal tissue, and correlated to CK5 expression (p=0.0368). However, this score was not associated with expression of CK14, CK18 or tumor size. CK18 expression was statistically significant when compared to the early age (p=0.0368). In this study, 14 cases relapsed, but this outcome was not associated to clinical variables, Ki67 score or any CKs expression. CK5 expression in basal cells did not present statistical differences in relation to CK18 (p=0.3438) and CK14 (p=0.3105) expression. CK14 and CK18 expression were mutually exclusive (p=0.0022).  Conclusions: We concluded that, although inserted in a distinct environment and prone to an epithelial mesenchymal influence, the ductal epithelium of FAs exhibited a CKs profile and proliferation similar to the progenitor cells profile in normal breast tissue, suggesting a preserved differentiation process.